SOURCE-BASED WRITING AMONG UNDERGRADUATE STUDENTS: PERSPECTIVE AND CHALLENGES - Ansas, Velayeti Nurfitriana; Sukyadi, Didi (UPI Press, 2019)
The level of scientific publications of Indonesian students at the international level is still very minimal. Even when compared to Malaysia and Thailand, Indonesia is still lagging behind. The Ministry of Research, Technology and Higher Education targets that in 2019 Indonesia will reach 30,000 international publications. Therefore, students' interest in writing must be increased, especially writing based on sources. Therefore, this study would like to find students' perspectives and perceived challenges in writing based on sources. This research was based on a case study. Â The research involved 68 students from one of the state universities in Bandung, and it analyzed 20 selected scientific papers written by students. The instruments for data collection included questionnaire and observation. The results of this study found that 59% of students perceived that writing scientific papers is very difficult. The students found it difficult to find suitable sources for writing material and develop their ideas. They tended to use articles as the sources from the internet whose originality is unclear. One reason this happens was because 80% of students did not know where to find or get indexed journals to use as references for their writing. In addition, many students also preferred not to use journals that were majorly English-based because of their limitation of English skills. The implication is that students should be given further understanding of how to access journals and use reference sources in writing. It is expected that every lecturer will give more source-based writing assignments so that the ability of students to write and develop ideas based on existing sources can be further improved.